Prevalence of non-communicable chronic diseases and associated factors in deaf people - Verônica Francisqueti Marquete; Sonia Silva Marcon; Inacia Sátiro Xavier de França; Elen Ferraz Teston; Magda Lúcia Felix de Oliveira; Maria Antonia Ramos Costa; Rebeca Rosa de Souza; Patrícia Chatalov Ferreira (Revista Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To analyze the prevalence and factors associated with non-communicable chronic diseases in deaf people. Methods: Cross-sectional study with 110 deaf people in Maringá-Paraná, selected using the snowball sampling technique. Data were collected from February to August 2019, using a structured instrument; and, in the analysis, multiple logistic regression was used. Results: The self-reported prevalence of chronic diseases was 43.6%, the most frequent being: arterial hypertension (12.7%), depression (6.4%), diabetes mellitus (5.4%), respiratory disease (5.4%) and hypothyroidism (4.5%). Using health services for routine consultations was significantly associated with being bimodal bilingual. The only risk behavior significantly associated with chronic disease was excessive consumption of sweet foods. Conclusion: The prevalence of chronic diseases in this population may be higher than that found, as there is a possibility of underdiagnosis due to the low demand for routine consultations and the difficulty of communication with health professionals.